Pedagogical control in modular education - Zatyneiyko, A.M.; Karmanova, A.A. (Ye.A.Buketov Karaganda State University Publ., 2014)
The article reviews the questions of pedagogical control in modular teaching as one of the methods of improving the quality of education. The author analysed the researches of native and foreign scientists on problems of control and assessment of education quality and described the main methods and forms of control in modular education. The article specificates the general criteria of forming module content.
Модульдік оқытуда педагогикалық бақылау
Педагогический контроль в модульном обучении
Keywords: pedagogical control; modular teaching; modular technologies; assessment of education quality; testing; methods of control; forms of control; module content; modular programs